Repellent and Lethal Activities of Extracts From Fruits of Chinaberry (Melia azedarach L., Meliaceae) Against Triatoma infestans - Dadé, Martín; Zeinsteger, Pedro; Bozzolo, Facundo; Mestorino, Nora (Frontiers in Veterinary Science, 2018)
Triatoma infestans is the principal vector of Trypanosoma cruzi, parasite responsible of Chagas´s Disease transmission in Argentina. Pyrethroids have become common pesticides for the control of T. infestans but increasing resistance encourages the search of new alternatives and the use of natural products for biological control arises as a new strategy. Melia azedarach L. is originated from the Himalaya´s region and several compounds are part of its rich phytochemistry. Folk medicine of the plant is due to its repellent and insecticidal activities. Aims of this work were to evaluate the repellent activity of methanolic and acetonic extracts from fruits of M. azedarach by means of the area preference method of fifth and first nymph stages as well as to test the acute lethal effect of the more repellent extract by means of direct application on cuticle on both stages. For repellence, qualitative filter papers were divided into two halves, one treated with methanolic (ME) or acetonic (AC) extract and the other without treatment. Controls were impregnated half with methanol or acetone and half without the solvents. One nymph was located in each Petri or well and repellence percentage was determined. For the lethal effect, fasted and fed to repletion 5th stage nymphs were topically administered with different concentrations of AC and deaths were registered after 24, 48, 72, 96 and 120 hours. Phytochemical analysis of extracts was performed as well. AC demonstrated high repellent activity (100%, both stages), whereas ME extract activity was slight (10-21%). AC extract was selected for lethal assays due to early repellent activity. Fed to repletion nymphs were more sensitive to the lethal activity of the extract when compared to fasted nymphs (LD50: 11.5 vs 23.1 µg/insect, respectively). Phytochemistry assays of extracts showed a higher concentration of flavonoids, alkaloids and triterpenes for AC. Considering these results, next assays will include the test of Melia azedarach extract on T. infestans that are resistant to pyrethroids for a possible synergism between AC and the pesticides.